2005
DOI: 10.1002/ejoc.200500054
|View full text |Cite
|
Sign up to set email alerts
|

Cooperative Intramolecular Hydrogen Bonding Effect and Basicity –An Ab Initio and DFT Study of the Superbasic Properties ofN‐[(Dimethylamino)alkyl]‐2,3‐diaminocycloprop‐2‐ene‐1‐imines

Abstract: The MP2(fc)/6‐311+G**//HF/6‐31G* and B3LYP/6‐311+G**//HF/6‐31G* calculations show that N‐[3‐(dimethylamino)propyl] and N‐[4‐(dimethylamino)butyl] derivatives of 2,3‐diamino‐cycloprop‐2‐ene‐1‐imine (CPI) possess high gas phase proton affinities (PA) and pronounced basicities in acetonitrile (MeCN). Tris[N‐dimethylaminopropyl(‐butyl)]‐CPI derivatives achieve superbasic PA and pKa values. The reason behind these remarkable features is the stability of the resulting conjugate acids. They are stabilized by aromatiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
23
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 40 publications
(23 citation statements)
references
References 40 publications
(30 reference statements)
0
23
0
Order By: Relevance
“…The intramolecular hydrogen bonding (IHB) motif has been employed for this purpose too, being particularly useful if utilized in a cooperative way by including multiple hydrogen bonds. [30][31][32] Special interest has been focused on neutral organic bases known as "proton sponges" possessing chelating proton acceptor functionalities. The archetypal compound is Alder's DMAN [1,8-bis(dimethylamino)naphthalene] synthesized some 35 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…The intramolecular hydrogen bonding (IHB) motif has been employed for this purpose too, being particularly useful if utilized in a cooperative way by including multiple hydrogen bonds. [30][31][32] Special interest has been focused on neutral organic bases known as "proton sponges" possessing chelating proton acceptor functionalities. The archetypal compound is Alder's DMAN [1,8-bis(dimethylamino)naphthalene] synthesized some 35 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…[31][32][33][34][35] The intramolecular hydrogen bonding (IMHB) motif proved very useful for this purpose too, [36,37] being particularly effective if utilized in a cooperative way by including multiple hydrogen bonds. [38][39][40] A lot of attention has been focused on neutral organic bases known as "proton sponges" possessing chelating proton-acceptor functionalities. The archetypal proton sponge is Alder's DMAN [1,8-bis(dimethylamino)naphthalene] synthesized some 35 years ago.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, owing to their strong basicities, guanidines serve as useful catalysts in a wide range of base‐catalyzed organic reactions (Raab et al, ; Glasovac et al, ; Ishikawa, ) and their gas‐phase basicities were experimentaly determined (Amekraz et al, ; Raczynska et al, ; Glasovac et al, , ). Finally, in line with the preceding properties, the guanidine fragment was employed as an essential building block in computational tailoring of superbases (Maksic & Kovacevic ; Howard et al, ; Kovacevic, Glasovac, & Maksic, ; Kovacevic & Maksic, ; Kovacevic et al, ; Raab et al, ; Gattin et al, ; Maksic, Kovacevic, & Vianello, ; Baric, Dragicevic, & Kovacevic, ]. In the course of these studies, considerable attention has been devoted to molecular modifications of the parent molecule leading to an enhancement of its basicity.…”
Section: Guanidinesmentioning
confidence: 99%
“…From examination of Scheme 6, the reverse is clearly evident when comparing endocyclic imines and amines. Maksic & Kovacevic (1999); Gattin, Kovacevic, & Maksic (2005), Baric, Dragicevic, & Kovacevic (2014); S Ciftcio glu & Trindle (2014) used quantum chemical methods to explore the potentialities of iminocyclopropene ring in building strong organic bases (Scheme 8). It is found that the parent iminocyclopropene itself, 1, with a proton affinity of ca 960 kJ/mol is rather a strong base.…”
Section: Cyclic Iminesmentioning
confidence: 99%